Crafting your edge for today's job market : using the BE-EDGE method for consulting cases and capstone projects - Ivy, Julia (Emerald Publishing Limited, 2019)
Are you looking to cut through the crowd of graduate job-seekers? To craft your edge in the saturated job market? Then you need the BE-EDGEMethod. The BE-EDGE Method provides a step-by-step guide that connects job seekers to target employers through a process of case consulting. It creates an opportunity for the new or established professional to carve out their own space in an industry of choice, by establishing a relationship of trust with and proving their value to an industry insider.The method shows readers how to:Elucidate their professional CORE, strategically identifying a space in the market that will best fit their multidimensional profile and selecting a case to work on; Develop TRUST with an industry insider on the basis of deep understanding and storytelling--as an industry researcher, company biographer, and case writer; Generate VALUE for a company by making a concrete contribution and offering action-based solutions in the form of a consulting case report; andExcite insiders with the candidate's fit for a company and their potential to add value in the industry.These steps allow the BE-EDGE Method to help young graduates to enhance their employability, as well as helping life-long learners to redefine and craft their own space in the market when looking to change careers. Including testimonials from students of this method, this book is unmissable for anyone looking to create their own space in industry.